A liberal preoperative fasting regimen improves patient comfort and satisfaction with anesthesia care in day-stay minor surgery - Bopp, Christian; Hofer, Stefan; Klein, A.; Weigand, Markus A.; Martin, E.; Gust, R. (Minerva Anestesiologica, 2011)
BACKGROUND: The aim of this study was to evaluate whether a single preoperative limited oral intake of a carbohydrate drink could improve perioperative patient comfort and satisfaction with anesthesia care in elective day-stay ophthalmologic surgery. METHODS:A single-center, prospective, randomized clinical trial was conducted in a university hospital. The study included ASA I-III patients undergoing ophthalmologic surgery. Patients undergoing both general anesthesia and local anesthesia were included in the study. The control group fasted in accordance to nil per os after midnight, while patients in the experimental group received 200 mL of a carbohydrate drink 2 h before the operation. Both groups were allowed to drink and eat until midnight ad libitum. Patient characteristics, subjective perceptions, taste of the drink, and satisfaction with anesthesia care were ascertained using a questionnaire administered three times: after the anesthesiologist’s visit, before surgery and before discharge from the ward to assess patient comfort. An analysis of variance and the Mann-Whitney U-test were used for statistical analysis. RESULTS: A total of 123 patients were included and 109 patients were randomly assigned to one of two preoperative fasting regimens. Patients drinking 200 mL 2 h before surgery were not as hungry (P<0.05), not as thirsty preoperatively (P<0.001) and not as thirsty after surgery (P<0.05), resulting in increased postoperative satisfaction with anesthesia care (P<0.05).CONCLUSION: Standardized limited oral preoperative fluid intake increases patient comfort and satisfaction with anesthesia care and should be a part of modern day-stay ophthalmologic surgery.
Gesehen am 02.06.2022